2017
DOI: 10.1186/s12916-017-0964-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomere tracking from birth to adulthood and residential traffic exposure

Abstract: BackgroundTelomere attrition is extremely rapid during the first years of life, while lifestyle during adulthood exerts a minor impact. This suggests that early life is an important period in the determination of telomere length. We investigated the importance of the early-life environment on both telomere tracking and adult telomere length.MethodsAmong 184 twins of the East Flanders Prospective Twin Survey, telomere length in placental tissue and in buccal cells in young adulthood was measured. Residential ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 58 publications
1
52
1
Order By: Relevance
“…34 Further, the authors found associations between residential traffic exposure at birth and accelerated telomere shortening in the first two decades of life. 34 There have been several longitudinal studies of the influence of traffic-related air pollution on lung function in early development versus later in life. 35,36 For example, a study of 2307 children from the Oslo Birth Cohort found that increased early life and lifetime exposure to PM 10 and NO 2 were associated with reduced expiratory flow measurements, with exposure in the first year of life having slightly stronger effects.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…34 Further, the authors found associations between residential traffic exposure at birth and accelerated telomere shortening in the first two decades of life. 34 There have been several longitudinal studies of the influence of traffic-related air pollution on lung function in early development versus later in life. 35,36 For example, a study of 2307 children from the Oslo Birth Cohort found that increased early life and lifetime exposure to PM 10 and NO 2 were associated with reduced expiratory flow measurements, with exposure in the first year of life having slightly stronger effects.…”
Section: Discussionmentioning
confidence: 95%
“…A longitudinal twin study that measured telomere length in prenatal placenta and buccal cells in young adulthood found inverse associations between traffic‐related air pollution and telomere length . Interestingly, the authors found that residential traffic exposure at the birth address was significantly and inversely associated with telomere length ranking between birth and adulthood; however, residential traffic exposure in adulthood was not associated with telomere length . Further, the authors found associations between residential traffic exposure at birth and accelerated telomere shortening in the first two decades of life .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…80 Interestingly, the association between the distance that pregnant mothers lived to a major road and TL persisted when telomeres in buccal cells were evaluated from the same individuals but now during young adulthood (mean age (SD) of 22.6 (3.1) years). 81 An Italian study 82 Evidence of occupational and environmental exposures (based on the home address) to chemicals and air pollutants in relationship with TL have been documented before. 16,84 However, in this review we add newly identified studies that extend the evidence of the association between TL and particulate matter exposure as previously reviewed by Martens and Nawrot.…”
Section: Residential Landscape and Telomere Lengthmentioning
confidence: 99%